2022
DOI: 10.21037/atm-22-732
|View full text |Cite
|
Sign up to set email alerts
|

Integrative bioinformatics analysis of potential therapeutic targets and immune infiltration characteristics in dilated cardiomyopathy

Abstract: Background: Dilated cardiomyopathy (DCM) is currently the major cause of systolic heart failure. This study explored potential therapeutic targets and investigated the role of immune cell infiltration in DCM.Methods: Three DCM datasets (GSE3585, GSE9800, and GSE84796) from the Gene Expression Omnibus (GEO) database were merged into an integrated dataset, and batch effects were removed.Differentially expressed genes (DEGs) were screened and the associations between gene co-expression modules and clinical traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
1
12
1
Order By: Relevance
“…Different from previous studies 19 , 20 , our enrichment analysis, in this study, for DEGs revealed that multiple enrichment items were significantly involved in immune response. Regulation of memory T cell differentiation, including regulation of T cell mediated cytotoxicity and immunological memory formation, has been mainly enriched in biological process.…”
Section: Discussioncontrasting
confidence: 99%
“…Different from previous studies 19 , 20 , our enrichment analysis, in this study, for DEGs revealed that multiple enrichment items were significantly involved in immune response. Regulation of memory T cell differentiation, including regulation of T cell mediated cytotoxicity and immunological memory formation, has been mainly enriched in biological process.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, similar to previous studies [19,20] , our enrichment analysis for DEGs revealed that multiple enrichment items were signi cantly involved in immune response. Regulation of memory T cell differentiation, including regulation of T cell mediated cytotoxicity, immunological memory formation, and so forth, has been mainly enriched in biological process.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with previous studies, SERPIAN3 presented the diagnosis value (38) in HF, and this work expanded its scale into DCM with the same point as Asakura and Kitakaze (39). Furthermore, Yang et al (40) emphasizes the therapeutic value of FRZB, and our study expands its treatment potential to diagnosis value. Regarding FCN3, though studies pay attention to the diagnosis value for HF (41), no study reports the diagnosis value for DCM to our knowledge.…”
Section: Discussionmentioning
confidence: 59%